The sexy science of The big bang theory : essays on gender in the series - Farghaly, Nadine, 1981-; Leone, Eden (McFarland & Company, Inc., Publishers, 2015)
"One of CBS's most successful shows, The Big Bang Theory's mix of humor, nerdy protagonists, sexy female leads and quirky characters have brought the series international acclaim. This collection of new essays explores sexual themes in The Big Bang Theory, interpreted through various critical lenses"--